A robust and reliable routing based on multihop information in industrial wireless sensor networks. (2015) - Zolfaghari, Dariush; Taheri, Hassan; Rezaie, A. Hossein; Rezaei, Mohsen
Due to considerable noise in the industrial environments, wireless packet transmission is usually unreliable. Designing an efficient routing algorithm for these environments poses significant challenges. Current routing algorithms consider the quality of service parameters such as node energies and delay, but packet losses need a novel strategy to compensate for the decline in signal to noise ratio (SNR) in noisy industrial environments. The proposed routing algorithm is based on multihop neighbour information. The multihop neighbour nodes provide vital information for the source node, enabling it to select the proper relay node. In noisy channel conditions the transmitted packets should meet the deadline and be delivered to the sink node on time. Performance evaluation via simulations indicates significant improvement in reliability, lifetime of network, and realtime performance. The proposed algorithm is more robust than previous methods. The most beneficial features of the proposed algorithm are its uniform distribution of energy among nodes and deliverance of deadline packets with the lowest losses.